Philippines agreed to sign regional seed cooperation (seed without border aggrement) - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
Policy forum, exposure visit by high ranking delegations to South Asia, webinars on seed system, desk studies on seed system and position paper have led to Philippines agreeing to sign.